Diffusion Kurtosis Imaging Detects Microstructural Alterations in Brain of α-Synuclein Overexpressing Transgenic Mouse Model of Parkinson's Disease: A Pilot Study - Khairnar, Amit; Latta, Peter; Drazanova, Eva; Ruda-Kucerova, Jana; Szabó, Nikoletta; Arab, Anas; Hutter-Paier, Birgit; Havas, Daniel; Windisch, Manfred; Sulcova, Alexandra; Starcuk, Zenon; Rektorova, Irena (Neurotoxicity research, 2015)
Evidence suggests that accumulation and aggregation of α-synuclein contribute to the pathogenesis of Parkinson's disease (PD). The aim of this study was to evaluate whether diffusion kurtosis imaging (DKI) will provide a sensitive tool for differentiating between α-synuclein-overexpressing transgenic mouse model of PD (TNWT-61) and wild-type (WT) littermates. This experiment was designed as a proof-of-concept study and forms a part of a complex protocol and ongoing translational research. Nine-month-old TNWT-61 mice and age-matched WT littermates underwent behavioral tests to monitor motor impairment and MRI scanning using 9.4 Tesla system in vivo. Tract-based spatial statistics (TBSS) and the DKI protocol were used to compare the whole brain white matter of TNWT-61 and WT mice. In addition, region of interest (ROI) analysis was performed in gray matter regions such as substantia nigra, striatum, hippocampus, sensorimotor cortex, and thalamus known to show higher accumulation of α-synuclein. For the ROI analysis, both DKI (6 b-values) protocol and conventional (2 b-values) diffusion tensor imaging (cDTI) protocol were used. TNWT-61 mice showed significant impairment of motor coordination. With the DKI protocol, mean, axial, and radial kurtosis were found to be significantly elevated, whereas mean and radial diffusivity were decreased in the TNWT-61 group compared to that in the WT controls with both TBSS and ROI analysis. With the cDTI protocol, the ROI analysis showed decrease in all diffusivity parameters in TNWT-61 mice. The current study provides evidence that DKI by providing both kurtosis and diffusivity parameters gives unique information that is complementary to cDTI for in vivo detection of pathological changes that underlie PD-like symptomatology in TNWT-61 mouse model of PD. This result is a crucial step in search for a candidate diagnostic biomarker with translational potential and relevance for human studies.
Keywords: Animals; myši transgenní; zobrazování difuzních tenzorů; Parkinson’s disease; Parkinsonova nemoc; α-Synuclein; alpha-Synuclein; Mice, Transgenic; difuzní magnetická rezonance; pohybová aktivita; lidé; Mice; Pilot Projects; pilotní projekty; mozek; myši; Male; modely nemocí na zvířatech; Transgenic mice; Brain; Diffusion kurtosis imaging; Diffusion Tensor Imaging; Diffusion Magnetic Resonance Imaging; Disease Models, Animal; Motor Activity; TNWT-61; alfa-synuklein; zvířata; mužské pohlaví; Parkinson Disease; TBSS; Humans